Super-enhancers in hepatocellular carcinoma: regulatory mechanism and therapeutic targets - Xuejin Lu; Meizi Zhu; Xingyue Pei; Jinhu Ma; Rui Wang; Yi Wang; Shuwen Chen; Yan Yan; Yaling Zhu (Cancer Cell International)
Abstract Super-enhancers (SEs) represent a distinct category of cis-regulatory elements notable for their robust transcriptional activation capabilities. In tumor cells, SEs intricately regulate the expression of oncogenes and pivotal cancer-associated signaling pathways, offering significant potential for cancer treatment. However, few studies have systematically discussed the crucial role of SEs in hepatocellular carcinoma (HCC), which is one of the most common liver cancers with late-stage diagnosis and limited treatment methods for advanced disease. Herein, we first summarize the identification methods and the intricate processes of formation and organization of super-enhancers. Subsequently, we delve into the roles and molecular mechanisms of SEs within the framework of HCC. Finally, we discuss the inhibitors targeting the key SE-components and their potential effects on the treatment of HCC. In conclusion, this review meticulously encapsulates the distinctive characteristics of SEs and underscores their pivotal roles in the context of hepatocellular carcinoma, presenting a novel perspective on the potential of super-enhancers as emerging therapeutic targets for HCC.